Heterogeneous skills and homogeneous land: Segmentation and agglomeration - Matthias Wrede (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2012)
This paper analyzes the effect of skill heterogeneity on regional patterns of production and housing in the presence of pecuniary externalities within a general-equilibrium framework, assuming monopolistic competition in intermediate goods markets. It shows that the interplay of heterogeneous skills and comparatively homogeneous land demand triggers skill segmentation and agglomeration. The core region that is more attractive to high skilled workers has a disproportionately large share of production at all levels of the supply chain. The paper extensively discusses welfare increasing tax policies. This paper also briefly studies how trade in intermediate goods and endogenous land demand affect segmentation and agglomeration.
Keywords: R12; R13; R14; H22; 330; skill heterogeneity; land use; sorting; agglomeration; Regionales Cluster; Bodennutzung; Qualifikation; Regionalökonomik; Allgemeines Gleichgewicht; Theorie